Identification of Maximal Affine Term Structure Models - COLLIN‐DUFRESNE, PIERRE; GOLDSTEIN, ROBERT S.; JONES, CHRISTOPHER S. (Journal of Finance, 2008)
ABSTRACT Building on Duffie and Kan (1996) , we propose a new representation of affine models in which the state vector comprises infinitesimal maturity yields and their quadratic covariations. Because these variables possess unambiguous economic interpretations, they generate a representation that is globally identifiable . Further, this representation has more identifiable parameters than the “maximal” model of Dai and Singleton (2000) . We implement this new representation for select three‐factor models and find that model‐independent estimates for the state vector can be estimated directly from yield curve data, which present advantages for the estimation and interpretation of multifactor models.